(untitled) (Innovaciones Educativas, 2024)
University students seek to develop practical skills to prepare them for real-world challenges. These expectations confront traditional pedagogical approaches and drive the adoption of new approaches that are oriented toward addressing problems in today’s society that require innovative solutions. In light of the above, university students were asked to implement an educational innovation aimed at designing solutions to stimulate memory and recall of information in older adults. This educational innovation applied the challenge-based learning methodology and a design thinking process. The participants were 20 students, 7 health professionals, and 14 older adults, and the instruments used were semi-structured interviews and an evaluation questionnaire of the educational innovation. The results showed that the students positively evaluated the educational innovation and the achievement of designing innovative products to improve memory and retrieval skills in older adults. In conclusion, the educational innovation was a successful proposal to encourage university students to engage in their learning, develop work-related skills, and raise awareness of the problems of old age.